134k views
16 votes
3(4+12x)-6(2x+3)=36+2(3x+2)

User KingBob
by
5.3k points

2 Answers

10 votes

Answer:

23/9

Explanation:

3(4 + 12x) - 6(2x + 3) = 36 + 2(3x + 2)

12 + 36x - 12x - 18 = 36 + 6x + 4

12 - 18 - 36 - 4 = -36x + 12x + 6x

-46 = -18x

x=46/18

x=23/9

User Allen Jee
by
5.6k points
7 votes

Answer:

x= 23/9

Explanation:

(12 + 36x) - (12x + 18) = 36 + (6x + 4)

(12 - 18) + (36x - 12x) = 36 + 4 + 6x

-6 + 24x = 40 + 6x

-6 + 18x = 40

18x = 46

x = 46/18

x = 23/9

User Daniel De Paula
by
4.6k points